Reconstruction of Maqâshid al-Syarî`ah As An Approach to Constitutional Law in Overcoming Crime in Indonesia - Suparmin, Sudirman; Ramadani, Ramadani (Madania: Jurnal Kajian Keislaman, 2022)
In Indonesia, the crime rate still reaches 1.01% in 2020, but crime still exists and is a state concern. The purpose of this study is aimed to analyze the offer of maqâshid al-syarî`ah as a solution in overcoming crime in Indonesia. This study is qualitative research in nature with a literature review approach. The object analyzed is Article 29 of UUD 1945 which is analyzed with the concept of maqâshid al-syarî`ah in the study of Islamic law. The results of this study describe that the maqâshid al-syarî`ahconcept can be a solution to overcome crime in Indonesia as its concept regulates various things including God's purposes (qashdu al-syâri') and mukallâf goals (qashdu al-mukallâf) as well as the perspective of constitutional law in the crime in Indonesia. The state regulates matters contained in the state of the fundamental norm, namely the constitution contained in Article 29 of UUD 1945. This article uses a religious approach as a basic rule to regulate the life of the Indonesian legal community so that they live a good life and do not commit the crimes contained in the UUD 1945. Internalization of maqâshid al-syarî`ah in constitutional law is an alternative to protecting citizens from various crimes. Di Indonesia, angka kejahatan masih mencapai 1.01% pada tahun 2020,  artinya kejahatan masih ada dan menjadi perhatian negara. Tujuan penelitian ini adalah menganalisis tawaran  maqâshid al-syarî`ah sebagai solusi dalam mengatasi kejahatan di Indonesia. Penelitian ini merupakan penelitian kualitatif dengan pendekatan kajian pustaka. Objek yang dianalisis adalah  pasal 29 UUD 1945 yang dianalisis dengan konsep maqâshid al-syarî`ah dalam kajian hukum Islam. Hasil penelitian ini menguraikan bahwa konsep maqâshid al-syarî`ah dapat menjadi solusi untuk mengatasi kejahatan di Indonesia sebagaimana konsep maqashid syariah mengatur berbagai aspek diantaranya yaitu tujuan Allah (qashdu al-syâri’) dan tujuan mukallâf (qashdu al-mukallâf) dan begitu juga dengan perspektif hukum tata negara dalam melihat kejahatan di indonesia. Negara mengatur hal yang terdapat pada staats fundamental norm, yaitu konstitusi yang terdapat di dalam UUD 1945 pasal 29. Pasal ini menggunakan pendekatan agama sebagai aturan dasar untuk mengatur tata kehidupan masyarakat hukum Indonesia agar menjalankan kehidupan dengan baik dan tidak melakukan kejahatan sebagaimana yang tertuang di dalam UUD 1945. Internalisasi maqâshid al-syarî`ah dalam hukum tatanegara menjadi alternatif dalam menjaga warga negara dari berbagai kejahatan.